Biodiversity of fresh water algae from Guindy campus of Chennai, India - Arulmurugan, P; Nagaraj, S; Anand, N (Journal of Ecobiotechnology, 2011)
<!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]--> The present work deals with the 35 fresh water algal samples and description of 62 taxa of biodiversity of fresh water algae from University of Madras Guindy campus of Chennai. Collections of 35 fresh water algal samples were carried out during the month of December 2010 to April 2011. Samples were examined in the laboratory and identified. The following algae were present Chlorococcum(1), Elakatothrix (1), Chlorella (1), Palmellococcus (1), Tetraedron (1), Polyedriopsis (1), Chodatella (1), Oocystis (2), Coelastrum (1), Scenedesmus quadricauda (Turpin) Breb. var. longispina (Chodat) G. M. Smith, Scenedesmus (3), Microspora (1), Rhizoclonium (1), Trentipholia (2), Closterium (1), Cosmarium (5) of Chlorophyceae, Cyclotella (1), Fragilaria (2), Achnanthes (1), Amphora (1), Navicula (5), Pinnularia (1), Hantzschia (1) and Nitzschia (1) of Bacillariophyceae and Microcystis (1), Chroococcus (3) Chroococcidiopsis (1), Gloeocapsa (2), Gleocapsopsis (1), Aphanotheace (1), Chlorogloea (2), Oscillatoria (3), Phormidium (3), Lyngbya (3), Microcoleus (1), Microchaete tenera (1), Calothrix (1), Camptylonema (1) and Hapalosiphon (1) of Cyanophyceae were recorded. Algae are described with photographs.